"Fools for the sake of Christ": Missional hermeneutics and praxis in the Corinthian correspondence. (April 2015) - Barram, Michael
Paul's rhetoric in the Corinthian correspondence suggests that at least some of the Corinthians understood wisdom, power, freedom, and knowledge as being at the heart of Christian identity and practice in the world. Paul counters each of those terms hermeneutically, missionally—underscoring the import of foolishness, weakness, slavery, and love—with respect to his mission in the world and their own. Love, as explicated by Paul, helps to clarify why foolishness, weakness, and slavery trump wisdom, power, freedom, and knowledge. Apart from love, focusing on wisdom, power, freedom, or knowledge can become self-referential. Only in love can those characteristics move beyond themselves for the good—the building up—of others. Paul's corrective metaphors for missional hermeneutics and praxis—foolishness, weakness, slavery, and love—represent concrete and counter-intuitive ways in which the mission Dei has been and must be manifested. In the process of exploring these issues, the article offers extended reflections on the implications of Paul's hermeneutical reasoning for contemporary mission today.